Overeducation in Trinidad and Tobago's Labour Market: A Quantile Regression Approach - Roshnie Doon (Global Labor Organization (GLO), 2021)
This study examines the impact that over-education has on the earnings of private and public sector workers in Trinidad and Tobago. Using individual person's data from the Continuous Sample Survey of the Population (CSSP) for the period 1991-2015, the returns of over-educated workers is estimated using a simple Quantile Regression approach. The labour force comprises of a large amount of over-educated workers who hold secondary and university level qualifications. The returns of workers employed in high-income jobs seems to be falling throughout the entire 1991-2015 period, while that of low and middle-income workers improved during 2004-2009 but declined thereafter the 2010-2015 as Trinidad and Tobago entered an economic recession. In addition, even though the wage returns of over-educated men, improves over the wage distribution, those in low and high-income jobs degenerated consistently throughout the 1991-2015 period. When compared to that of women, the opposite is true as their returns tends to worsen across much of the wage distribution. With any improvement being observed during 1991-2009 by low-income women.
Keywords: C21; I21; I26; 330; Human Capital; Educational Mismatch; Returns to Over-education; Quantile Regression